ANALYSIS OF ONLINE LEARNING MEDIA ON PJOK LEARNING OUTCOMES - Dahlan Abdullah; Komang Ayu Krisna Dewi; Darmawanta Sembiring; Nursyamsi SY; I Putu Agus Dharma Hita (STKIP PGRI Situbondo, 2023)
Learning outcomes are a reference to see whether the learning process is going well or not. Whether or not learning outcomes are influenced by various factors, one of which is the learning media used. This study aims to determine the effect of Google Classroom learning media on PJOK learning outcomes. This research is an experimental research. This research was conducted at TP 45 State Vocational Schools from November 2021 to December 2021. The sample in this study were all students of TP 45 State Vocational Schools class XP1 and XP2 for the academic year 2021/2022 even semester, a total of 70 people. The results in this study are that there is no influence from Google Classroom learning media on PJOK learning outcomes